CONSONORM_HG: a new method of norm calculation for mid‐ to high‐grade metamorphic rocks. (8th October 2015) - Mathieu, L.; Trépanier, S.; Daigneault, R.
Abstract: The CONSONORM_HG norm provides a standardized solution to approximate metamorphic assemblages for mid‐ to high‐grade metamorphic rocks. Other applications for this norm include: (i) the standardized classification of metamorphic rocks; (ii) the interpretation of hydrothermal alteration using indices calculated from normative minerals; (iii) the estimation of the carbonate content of rocks, even when CO2 has not been analysed. CONSONORM_HG is designed for rocks dominated by silicates, Fe–Ti oxides or carbonates, and it approximates the main mineral assemblages of amphibolite, granulite, greenschist and blueschist facies metamorphic rocks. The norm calculates silicate assemblages using one of the three Al–Ca–NaK–FeMg tetrahedra, a convenient way of representing a large number of silicate assemblages, for each of the 17 P–T conditions modelled and based on the Fe–Mg–Mn composition of the sample. In addition to silicate minerals, CONSONORM_HG calculates Fe–Ti oxides and other accessory minerals from minor elements, sulphides from analysed sulphur and/or from analysed metals and also carbonates from analysed CO2 or from normative CO2 estimated from the loss on ignition. CONSONORM_HG also integrates many reactions to address silicon deficits, as well as quartz–carbonate reactions to approximate natural assemblages better. The normative calculation is validated using published whole‐rock analyses and petrographic descriptions and its various applications are discussed.